The Effect of Principal Leadership and School Culture through the Adiwiyata Program on the Environmental Awareness Character of SMAN 2 Blora Students. - Ghozali, Ilham; Kardoyo, Kardoyo; Oktarina, Nina (Educational Management, 2024)
This study aims to determine and analyze the effect of principal leadership and school culture on the environmental awareness character through the Adiwiyata program as a moderating variable. This research is important in term of determining the impact of the Adiwiyata program to the environment awareness since there are some other factors included especially at school students level. This research is a quantitative research conducted with a sample of 284 students at SMA N 2 Blora. Data were collected by questionnaire and documentation. The data were analyzed by multiple regression, T test and coefficient of determination. The results showed: (1) Principal leadership does not directly affect environmental awareness, (2) School culture does have a significant impact on environmental awareness, (3) Adiwiyata program does not moderate the effect of principal leadership on environmental awareness, and (4) Adiwiyata program does not moderate the effect of school culture on environmental awareness. The result of this research is in line with psychoanalysis theory by Sigmund Freud since the culture impact students’ character. The result of this research can be used as the one of the reference in implementing Adiwiyata program, also can be used as a reference in improving environmental awareness character. The impact of these independent variables can be improved in various ways, including: (1) increasing the interaction of the principal with students through environmental conservation activities, (2) integrating Adiwiyata program into the school culture that has been running, and (3) environment-based program to increase students' interest in environmental conservation